Efficacy of complementary medicine for nonsteroidal anti-inflammatory drug-induced small intestinal injuries: A narrative review. Issue 48 (3rd December 2021) - Cho, Minji; Bu, Youngmin; Park, Jae-Woo; Rahman, Hasanur; Ko, Seok-Jae
Abstract : Abstract: Nonsteroidal anti-inflammatory drug-induced small bowel injuries (NSIs) have been largely ignored for decades due to the focus on nonsteroidal anti-inflammatory drug gastropathy. With the visualization of the small intestines enabled by video capsule endoscopy, the frequency and severity of NSIs have become more evident. NSIs have a complex pathophysiology, and no effective preventive or treatment options have been proven. Complementary and alternative medicine (CAM) has been used to treat disorders of the small intestine, and more research on its effectiveness for NSIs has been conducted. We reviewed the current evidence and mechanisms of action of CAMs on NSI. Clinical and experimental studies on the effect of CAMs on NSIs were performed using 10 databases. Twenty-two studies (3 clinical and 19 in vivo experimental studies) were included in the final analysis involving 10 kinds of CAMs: bovine colostrum, Orengedokuto (coptis), muscovite, licorice, grape seed, wheat, brown seaweed, Ganoderma lucidum fungus mycelia, Chaenomeles speciosa (sweet) Nakai (muguasantie), and Jinghua Weikang capsule. The mechanisms of CAM include an increase in prostaglandin E2, reparation of the enteric nervous system, inhibition of pro-inflammatory cytokines, reduction of intestinal permeability and enteric bacterial numbers, decrease in oxidative stress, and modulation of small intestinal motility. CAM may be a novel alternative option for treating and preventing NSI, and further studies on human and animal models with relevant comorbidities are warranted.